2021
DOI: 10.3390/polym13101653
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Adhesion Analysis of 3D-Printed Continuous Carbon Fibre-Reinforced Composites

Abstract: Carbon fibre-reinforced materials are becoming more and more popular in various fields of industries because of their lightweight and perfect mechanical properties. Additive manufacturing technologies can be used for the production of complex parts from various materials including composites. Fused deposition modelling (FDM) is an excellent technology for the production of composite structures reinforced with short or continuous carbon fibre. In this study, modified FDM technology was used for the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In [ 24 ], it is stated that the crack propagation for FDM parts will take place between the two layers if the load is applied perpendicular to the print orientation. In [ 25 ], it was found that the load resistance can be increased by reducing the layer thickness, and with an increased shear area, the value of shear force increase proportionally, as in the case of O samples in this study. In [ 16 ], the authors stated that the infill density should be maximized in order to maximize the strength and resistance to failure.…”
Section: Effect Of the Contour Lines And Stress Distributionsupporting
confidence: 62%
“…In [ 24 ], it is stated that the crack propagation for FDM parts will take place between the two layers if the load is applied perpendicular to the print orientation. In [ 25 ], it was found that the load resistance can be increased by reducing the layer thickness, and with an increased shear area, the value of shear force increase proportionally, as in the case of O samples in this study. In [ 16 ], the authors stated that the infill density should be maximized in order to maximize the strength and resistance to failure.…”
Section: Effect Of the Contour Lines And Stress Distributionsupporting
confidence: 62%
“…Fused deposition modeling (FDM) 3D printing has been widely utilized in various industries due to its custom design and cost effectiveness [1][2][3][4][5][6][7][8]. FDM 3D printing products have formed by the layer-by-layer deposition, which exhibited anisotropic characteristic and drawbacks such as poor interlayer adhesion, incomplete printing, shrinkage and low dimension accuracy resulting in low mechanical performance and their structural failure [3,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…FDM 3D printing products have formed by the layer-by-layer deposition, which exhibited anisotropic characteristic and drawbacks such as poor interlayer adhesion, incomplete printing, shrinkage and low dimension accuracy resulting in low mechanical performance and their structural failure [3,5,[7][8][9]. The selection of filaments and the controlled printing conditions can be optimized for improving the drawbacks and obtaining superior mechanical performance of the FDM 3D printing products [1,2,[10][11][12]. Polymer filaments are feedstocks for the FDM 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…In this project, the influences of the main FFF printing parameters were studied by the characterization of different materials subjected to destructive uniaxial tensile tests [ 7 , 8 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Even though there is still not an abundant number of publications referring to these emerging technologies, with regard to specific processes using the FFF technique, a large number of studies have been conducted to analyze the behaviors of specimens using different criteria, highlighting the porosity [ 46 , 47 ], dimensional accuracy [ 48 , 49 , 50 ], influence of temperature [ 11 ] and the rheological behavior [ 51 ], coating and impregnation of reinforcement fibers [ 52 , 53 , 54 ], part distortion [ 55 , 56 ], Domingo-Espin et al on fatigue behavior [ 57 , 58 ], and bond formation [ 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%